Effects of Waves on the Spectral Anisotropy of the Transition Range in Solar Wind Turbulence - Hua Zhang; Xin Wang; Haochen Yuan (The Astrophysical Journal)
In the transition range of the solar wind turbulence, the magnetic spectrum has been observed to be strongly anisotropic with respect to the local mean field. However, the generation mechanism of the anisotropy remains not well understood. There are two typical types of waves existing in the transition range, including ion cyclotron waves (ICWs) and kinetic Alfvén waves (KAWs) propagating in the directions parallel and perpendicular to the magnetic field, respectively. In this work, we perform a statistical study about the effects of the waves on the spectral anisotropy of the transition range. We select 31 intervals from the measurements of Parker Solar Probe between 2018 and 2021. The magnetic helicity ( σ _m ) diagnosis is applied on the magnetic field data, and the wavelet coefficients with σ _m ≤ −0.5 and σ _m ≥ 0.4 are considered as signals of ICWs and KAWs, respectively. For the first time, we remove both ICWs and KAWs systematically from the power spectral density of magnetic field fluctuations and find that the magnetic spectral anisotropy in the transition range becomes significantly weaker. Specifically, the spectra in the quasi-parallel direction statistically get shallower, and the average spectral index changes from −5.68 ± 0.74 to −4.72 ± 0.56. By contrast, the spectra in the perpendicular direction get slightly steeper, and the index changes from −3.63 ± 0.34 to −3.95 ± 0.41. Moreover, the anisotropic scaling in the transition range is found to be ${k}_{\parallel }\sim {k}_{\perp }^{1.53± 0.33}$ . The new results will help to further understand the possible mechanisms that cause the spectral anisotropy in the transition range.